PENYULUHAN HUKUM PERJANJIAN BAGI HASIL DI BIDANG PERTANIAN ANTARA PENGGARAP DAN PEMILIK LAHAN (SAWAH) DI DESA KENCANA HARAPAN KECAMATAN LEBAK WANGI KABUPATEN SERANG - Ujang Hibar; Mohammad Hifni; Aris Setyanto Pramono (Yayasan Education and Social Center, 2023)
Community service activities on the agreement of profit sharing in agriculture in Kencana Village, Lebak Wangi District, aim to provide an understanding to the community about the importance of this agreement in establishing socio-economic relations between landowners and tenant farmers. The agreement allows the tenant farmers to cultivate the land with the permission of the landowners, based on agreed conditions and profit sharing. The main objective is to create fairness in land profit distribution and provide legal certainty to both parties. The method of community service activities involves conducting legal counseling on profit sharing agreements. The focus of the activities is on the profit-sharing system or